A comprehensive analysis of malaria transmission in Brazil - Carlos, Bianca C. [UNESP] (2019)
Malaria remains a serious public health problem in Brazil despite a significant drop in the number of cases in the past decade. We conduct a comprehensive analysis of malaria transmission in Brazil to highlight the epidemiologically most relevant components that could help tackle the disease. We consider factors impacting on the malaria burden and transmission dynamics including the geographical occurrence of both autochthonous and imported infections, the distribution and abundance of malaria vectors and records of natural mosquito infections with Plasmodium. Our analysis identifies three discrete malaria transmission systems related to the Amazon rainforest, Atlantic rainforest and Brazilian coast, respectively. The Amazonian system accounts for 99% of all malaria cases in the country. It is largely due to autochthonous P. vivax and P. falciparum transmission by mosquitoes of the Nyssorhynchus subgenus, primarily Anopheles darlingi. Whilst P. vivax transmission is widespread, P. falciparum transmission is restricted to hotspot areas mostly in the States of Amazonas and Acre. This system is the major source of P. vivax exportation to the extra-Amazonian regions that are also affected by importation of P. falciparum from Africa. The Atlantic system comprises autochthonous P. vivax transmission typically by the bromeliad-associated mosquitoes An. cruzii and An. bellator of the Kerteszia subgenus. An. cruzii also transmits simian malaria parasites to humans. The third, widespread but geographically fragmented, system is found along the Brazilian coast and comprises P. vivax transmission mainly by An. aquasalis. We conclude that these geographically and biologically distinct malaria transmission systems require specific strategies for effective disease control.